2002
DOI: 10.1210/mend.16.6.0846
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Liver Gene Expression Governed by TRβ

Abstract: Several metabolic processes in the liver are regulated by thyroid hormone (T3). Gene expression profiles of livers from normal and TRbeta-deficient mouse strains should allow the classification of rapid and sustained effects of T3, as well as identification of target genes that are dependent on TRbeta. The immediate and long-term T3 regulation of about 4000 genes in livers from hypo- and hyperthyroid wild-type and TRbeta-deficient mice was analyzed using cDNA microarrays. T3 was found to regulate more than 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 44 publications
6
44
0
Order By: Relevance
“…Flores-Morales et al recently performed microarray analyses of hepatic genes in wild-type and Thrb knockout mice that were treated with T 3 . They found that 155 hepatic genes were regulated after treatment for 2 h with T 3 in wild-type mice, whereas only 84 hepatic genes were regulated in Thrb knockout mice under the same conditions (Flores-Morales et al, 2002). They hypothesized that some of these effects could be due to Tr-β-isoform-specific effects.…”
Section: Transcription Patterns Of Thra and Thrb Knockout Micementioning
confidence: 99%
See 1 more Smart Citation
“…Flores-Morales et al recently performed microarray analyses of hepatic genes in wild-type and Thrb knockout mice that were treated with T 3 . They found that 155 hepatic genes were regulated after treatment for 2 h with T 3 in wild-type mice, whereas only 84 hepatic genes were regulated in Thrb knockout mice under the same conditions (Flores-Morales et al, 2002). They hypothesized that some of these effects could be due to Tr-β-isoform-specific effects.…”
Section: Transcription Patterns Of Thra and Thrb Knockout Micementioning
confidence: 99%
“…Recently, cDNA microarrays have been used to study the hormonal regulation of gene expression, including that by Trs (Meltzer, 2001;Feng et al, 2000;Miller et al, 2001;Flores-Morales et al, 2002). Previously, we used cDNA microarrays to study hepatic gene profiles in hypothyroid and hyperthyroid mice, and we identified more than 50 target genes, which are involved in a range of cellular pathways (Feng et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Flores-Morales et al [45] verified the effect of T3 on liver in mice with a targeted mutation in the TRβ gene. In accordance with the results of Weitzel [49], they reported that T3 regulates the expressions of functionally different sets of genes in temporally distinct ways.…”
Section: Transcriptomic Analysis Pertaining To the Actions Of Thyroidmentioning
confidence: 98%
“…This insulin-dependent phosphorylation allows for a switch of recruitment of NCoR between different groups of NRs and provides a mechanism for specific modulation of NR signaling depending on physiological conditions (fed vs fasted). While the effect of the S1460 phosphorylation on NCoR-TR interactions has not been studied yet, it could potentially also have important ramifications for TR signaling, as TH has been shown in different experimental paradigms to promote both lipid synthesis and fatty acid oxidation in the liver (Feng et al 2000, Flores-Morales et al 2002, Jackson-Hayes et al 2003, Oppenheimer et al 1991.…”
Section: Liver-specific Ncor Knockoutmentioning
confidence: 99%